Tabla de volumen para quercus copeyensis Muller en los robledales de San Gerardo de Dota, Costa Rica. - Jiménez., Wilberth (1990)
This article presents a volume table for an oak Quercus copeyensis Müller forest located in San Gerardo de Dota, Talamanca Range. For the elaboration of the volume table, several models were tested: the Logarithmic function showed the best approximation. Bases on the Logarithmic model, a one-variable volume table were constructed. The volume per hectare for Q. copeyensis was calculated based on a complete inventory carried out in the same location.